SOBRE LA ANALITICIDAD DEL SEMIGRUPO Co ASOCIADO A UN SISTEMA VISCOELÁSTICO - Santiago Ayala, Yolanda Silvia (2003)
We proved that the semigroup C0 associated to a viscoelastic system is analytic and exponentially stable.